Family-mediated exercise intervention (FAME): evaluation of a novel form of exercise delivery after stroke. - STOKES, EMMA; GALVIN, ROSEMARIE; O'GRADY, ELEANOR (My University, 2011)
BACKGROUND AND PURPOSE: Additional exercise therapy has been shown to have a positive impact on function after acute stroke and research is now focusing on methods to increase the amount of therapy that is delivered. This randomized controlled trial examined the impact of additional family-mediated exercise (FAME) therapy on outcome after acute stroke. METHODS: Forty participants with acute stroke were randomly assigned to either a control group who received routine therapy with no formal input from their family members or a FAME group, who received routine therapy and additional lower limb FAME therapy for 8 weeks. The primary outcome measure used was the lower limb section of the Fugl-Meyer Assessment modified by Lindmark. Other measures of impairment, activity, and participation were completed at baseline, postintervention, and at a 3-month follow-up. RESULTS: Statistically significant differences in favor of the FAME group were noted on all measures of impairment and activity postintervention (P<0.05). These improvements persisted at the 3-month follow-up but only walking was statistically significant (P<0.05). Participants in the FAME group were also significantly more integrated into their community at follow-up (P<0.05). Family members in the FAME group reported a significant decrease in their levels of caregiver strain at the follow-up when compared with those in the control group (P<0.01). CONCLUSIONS: This evidence-based FAME intervention can serve to optimize patient recovery and family involvement after acute stroke at the same time as being mindful of available resources.
PUBLISHED
Keywords: Physiotherapy; Stroke